Next generation sequencing using phenotype-based panels for genetic testing in inherited retinal diseases. (3rd July 2020) - Shah, Mital; Shanks, Morag; Packham, Emily; Williams, Jonathan; Haysmoore, Jesse; MacLaren, Robert E.; Németh, Andrea H.; Clouston, Penny; Downes, Susan M.
ABSTRACT: Introduction: Diagnostic next generation sequencing (NGS) services for patients with inherited retinal diseases (IRD) traditionally use gene panel based approaches, which have cost and resource implications. Phenotype-based gene panels use a targeted strategy with further testing protocols, if initial results are negative. We present the molecular findings of the Oxford phenotype-based NGS panels for genetic testing in IRD. Methods: Results of 655 consecutive patients referred for phenotype-based panel testing over 54 months were analysed to assess diagnostic yield. Results: Variants were identified in 450 patients (68.7%). The overall diagnostic yield from phenotype-based panels was 42.8%. The diagnostic yield was highest from panels representing distinct clinical phenotypes: Usher panel 90.9% and congenital stationary night blindness panel 75.0%. Retinitis pigmentosa/rod-cone dystrophy was the commonest presenting phenotype (n = 243) and Usher syndrome was the commonest presenting syndromic disease (n = 39). Patients presenting with late-onset (≥50 years) macular disease had a lower diagnostic yield (18.0%) compared with patients <50 years (24.2%). Additionally, a diagnostic yield of 1.8% was attributable to copy number variants. Conclusions: Phenotype-based genetic testing panels provide a targeted testing approach and reduce bioinformatics demand. The overall diagnostic yield achieved in this study reflects the wide range of phenotypes that were referred. This pragmatic approach provides a high yield for early-onset and clearly defined genetically determined disorders but clinical utility is not as clear for late-onset macular disorders. This phenotype-based panel approach is clinician-referrer orientated, and can be used as a front-end virtual panel, when whole genome sequencing is introduced into diagnostic services for IRD.